2007
DOI: 10.1111/j.1558-5646.2007.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Host Specificity Drives Reproductive Isolation Among Rna Viruses

Abstract: Ecological speciation hypotheses claim that assortative mating evolves as a consequence of divergent natural selection for ecologically important traits. Reproductive isolation is expected to be particularly likely to evolve by this mechanism in species such as phytophagous insects that mate in the habitats in which they eat. We tested this expectation by monitoring the evolution of reproductive isolation in laboratory populations of an RNA virus that undergoes genetic exchange only when multiple virus genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 59 publications
5
86
2
1
Order By: Relevance
“…In this study, for each cell type, the number and nature of the fixed nucleotide substitutions differed strikingly between the replicated evolved populations, in contrast with the homogeneity observed in their fitness values [28]. In addition, recent studies with bacteriophage 6 have shown that mutations conferring adaptation to a novel host tend to be characterized by negative pleiotropic effects on previous hosts [72][73][74]. However, RNA viruses can also evolve increased fitness in several cell types simultaneously, for instance, upon alternating-host evolution [42,71].…”
Section: Restrictions To Viral Adaptationcontrasting
confidence: 59%
“…In this study, for each cell type, the number and nature of the fixed nucleotide substitutions differed strikingly between the replicated evolved populations, in contrast with the homogeneity observed in their fitness values [28]. In addition, recent studies with bacteriophage 6 have shown that mutations conferring adaptation to a novel host tend to be characterized by negative pleiotropic effects on previous hosts [72][73][74]. However, RNA viruses can also evolve increased fitness in several cell types simultaneously, for instance, upon alternating-host evolution [42,71].…”
Section: Restrictions To Viral Adaptationcontrasting
confidence: 59%
“…It also raises important questions regarding lysogenic conversion of commensal strains to pathogenic strains at the level of virulence genes, as well as host specificity genes shuffling between "nonpathogenic" and "pathogenic" phages. Consistently, several studies have reported host range shifts in phages, a process that is efficiently improved by phage-bacterium coevolution (15,20,29,30,45). As S. aureus and CoNS share the same niche, we cannot exclude the possibility that such shifts might occur, resulting from the interplay between genetic alteration and environmental conditions.…”
Section: Resultsmentioning
confidence: 84%
“…The phenomenon of shifts in bacterial hosts has been observed for phage (Crill et al 2000;Duffy et al 2007;Ferris et al 2007), but so far as we know, not for plasmids. Several very valuable experimental evolution studies have demonstrated that plasmids can adapt to a bacterial host or that the host adapts to the plasmid, but none examined evolutionary changes in the plasmid's long-term host range (Bouma and Lenski 1988;Lenski et al 1994;Turner et al 1998;Dahlberg and Chao 2003;Dionisio et al 2005;Heuer et al 2007).…”
mentioning
confidence: 80%